Social Media as a Tool in Dental Public Health - Sourav Chandra Bidyasagar Bal1 , Radha Prasanna Dalai1, Darshan V.1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Facebook, WhatsApp, Instagram like social media are becoming an emerging instrument in the twenty-firstcentury to reach every person. Dentists can use any of the social media to give oral care to people. The dailyusers of the SM are more than one billion per day. If the dentist can make a beautiful blog regarding oral caremillions of people will get its benefits. Cost regarding uses of social media in recent days is approximatelyvery less and affordable by maximum people. It will beneficial to all age group people from small childrento elderly people. Various Social networks in recent year providing important massage like how we arecoordinating each other in developing society and promote our dental health with this media. When SM isused in a proper way it has a lot of beneficiary effect on people regarding dental and general health. Thefirst growth in dental science and its link with recent advance web technology bring the dental science to atop-level.